2014
DOI: 10.1371/journal.pone.0094180
|View full text |Cite
|
Sign up to set email alerts
|

An Oxidative Stress Mechanism of Shikonin in Human Glioma Cells

Abstract: Shikonin is a quinone-containing natural product that induces the apoptotic death of some cancer cell lines in culture through increasing intracellular reactive oxygen species (ROS). Quinone-based drugs have shown potential in the clinic, making shikonin an interesting compound to study. Our previous study found that shikonin induces apoptosis in neuroblastoma by induction of ROS, but its mechanism of action and scope of activity are unknown. In this study, we investigated the mode of oxidative stress of shiko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 25 publications
2
75
0
Order By: Relevance
“…Anti-cancer activity of several plant-derived compounds, such as isoalantolactone, matrine, and shikonin, has been shown to be mediated by reactive oxygen species (ROS) recently [55][56][57]. Additionally, many chemotherapeutic agents, such as cisplatin, osmium, beta-lapachone, and several other alkaloid compounds, have been identified that promote ROS generation as a component of their anti-tumor activity [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-cancer activity of several plant-derived compounds, such as isoalantolactone, matrine, and shikonin, has been shown to be mediated by reactive oxygen species (ROS) recently [55][56][57]. Additionally, many chemotherapeutic agents, such as cisplatin, osmium, beta-lapachone, and several other alkaloid compounds, have been identified that promote ROS generation as a component of their anti-tumor activity [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to develop novel strategies to increase the anticancer effects of colon cancer treatments. Lung cancer is considered to be the most common type of cancer in the world (11) and remains a major global health problem, accounting for 1.8 million annual mortalities worldwide in 2012 (12) and 17.8% of all cancer-associated mortalities in India in 2002 (13 cells was reported to able to inhibit apoptosis and induce cell proliferation, angiogenesis and metastasis, leading to a poor disease prognosis (14). The seed oil from C. inophyllum changes in color from yellow to green due to processing and storage conditions.…”
Section: Calophyllum Inophyllum L (C Inophyllum) Of the Familymentioning
confidence: 99%
“…The analyses of DNA damage and the cell cycle were performed by staining with PI and flow cytometry, as previously described (17,18). The cells (1x10 6 ) were cultured in 60 mm tissue culture dishes at 37˚C for 24 h. The RPMI 1640 culture medium (Hyclone; GE Healthcare Life Sciences, Logan, UT, USA) was replaced with fresh medium, and the cells were exposed to 0.60, 0.75 and 1.50x10 -3 % of the yellow pigment and 5.0, 12.5 and 25.0x10 -3 % of the green pigment at 37˚C for 48 h. Subsequently, the cells were pooled, washed with phosphate-buffered saline (PBS), fixed in a PBS-methanol (volume/volume, 1:2) solution at room temperature for 5 min and then incubated at 4˚C for at least 18 h. Following washing with PBS once, the cell pellets were stained with the PI solution supplemented with PBS, 40 µg/ml PI and 40 µg/ml of DNase-free RNase A (Sigma-Aldrich; Merck KGaA) for 30 min at room temperature in the dark and then analyzed using a Becton-Dickinson FACScan flow cytometer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Analysis Of Seed Oil Pigments From C Inophyllum Lmentioning
confidence: 99%
“…After drug treatment, the cells were collected, washed with phosphate-buffered saline (PBS), fixed in PBS-methanol (1:2, volume/volume) solution, and maintained at 4 • C for at least 18 h. After one PBS wash, the cell pellets were stained with a PI solution (PBS, 40 g/mL PI, and 40 g/mL DNase-free RNase A) for 30 min at room temperature in the dark and analyzed using a Becton-Dickinson FACScan flow cytometer (Franklin Lakes, NJ). At least 10,000 cells were counted per sample, and the DNA histograms were further evaluated using Modfit software on a PC workstation to calculate the percentage of cells in the various phases of the cell cycle and to quantify the cells with DNA damage (SubG 1 phase) [14].…”
Section: Dna Damage and Cell Cycle Analysismentioning
confidence: 99%